Ungrateful slaves? An examination of job quality and job satisfaction for male part‐time workers in the UK. (18th February 2020) - Warren, Tracey; Lyonette, Clare
Abstract: Research on part‐time work has concentrated over many decades on the experiences of women but male part‐time employment is growing in the UK. This article addresses two sizable gaps in knowledge concerning male part‐timers: are men's part‐time jobs of lower quality than men's full‐time jobs? Are male part‐timers more or less job‐satisfied compared to their full‐time peers? A fundamental part of both interrogations is whether men's part‐time employment varies by occupational class. The article is motivated by the large body of work on female part‐timers. Its theoretical framework is rooted in one of the most controversial discussions in the sociology of women workers: the "grateful slave" debate that emerged in the 1990s when researchers sought to explain why so many women expressed job satisfaction with low‐quality part‐time jobs. Innovatively, this article draws upon those contentious ideas to provide new insights into male, rather than female, part‐time employment. Based upon analysis of a large quantitative data set, the results provide clear evidence of low‐quality male part‐time employment in the UK, when compared with men's full‐time jobs. Men working part‐time also express deteriorating satisfaction with jobs overall and in several specific dimensions of their jobs. Male part‐timers in lower occupational class positions retain a clear "lead" both in bad job quality and low satisfaction. The article asks whether decreasingly satisfied male part‐time workers should be termed "ungrateful slaves?" It unpacks the "grateful slave" metaphor and, after doing so, rejects its value for the ongoing analysis of part‐time jobs in the formal labor market.